Indoor 3D Visible Light Positioning Analysis with Channel Estimation Errors - Bozanis, Dimitrios; Evgenidis, Nikos G.; Papanikolaou, Vasileios; Bouzinis, Pavlos S.; Tegos, Sotiris A.; Dowhuszko, Alexis A.; Diamantoulakis, Panagiotis D.; Karagiannidis, George K. (International Conference on Systems, Signals, and Image Processing, 2023)
Since radio-frequency signals are affected signifi-cantly by multipath fading, the localization accuracy they offer cannot meet the sixth generations (6G) demanding specifications. On the other hand, visible light positioning (VLP) has emerged as a low cost alternative that takes into account the highly deterministic channel characteristics of visible light communications to provide cm-level accuracy provided that the investigated spaces are adequately covered by LEDs. However, imperfect channel state information and modeling can lead to positioning errors. In this paper, localization accuracy is quantified in terms of channel estimation errors via low complexity lateration algorithm. The channel estimation errors can be caused by a variety of issues and the provided analysis is general so that it can be easily applied to a plethora of applications. Finally, Monte Carlo simulations validate the proposed method and offer valuable insights for the design and performance bounds of VLP systems.
CRIS-Team Scopus Importer:2023-08-11
Keywords: channel estimation errors; localization; visible light positioning (VLP)